The Potential of Toll-Like Receptors to Modulate Avian Immune System: Exploring the Effects of Genetic Variants and Phytonutrients - Rehman, Muhammad Saif-ur; Rehman, Saif ur; Yousaf, Wasim; Hassan, Faiz-ul; Ahmad, Waqas; Liu, Qingyou; Pan, Hongping (Frontiers in Genetics, 2021)
Toll-like receptors (TLRs) are pathogen recognition receptors, and primitive sources of innate immune response that also play key roles in the defense mechanism against infectious diseases. About 10 different TLRs have been discovered in chicken that recognize ligands and participate in TLR signaling pathways. Research findings related to TLRs revealed new approaches to understand the fundamental mechanisms of the immune system, patterns of resistance against diseases, and the role of TLR-specific pathways in nutrient metabolism in chicken. In particular, the uses of specific feed ingredients encourage molecular biologists to exploit the relationship between nutrients (including different phytochemicals) and TLRs to modulate immunity in chicken. Phytonutrients and prebiotics are noteworthy dietary components to promote immunity and the production of disease-resistant chicken. Supplementations of yeast-derived products have also been extensively studied to enhance innate immunity during the last decade. Such interventions pave the way to explore nutrigenomic approaches for healthy and profitable chicken production. Additionally, single-nucleotide polymorphisms in TLRs have shown potential association with few disease outbreaks in chickens. This review aimed to provide insights into the key roles of TLRs in the immune response and discuss the potential applications of these TLRs for genomic and nutritional interventions to improve health, and resistance against different fatal diseases in chicken.